Application of the Concept of Community Based Tourism in Walima Festival Tourism Objects, Bongo Village, Gorontalo Province - Sulila, Ismet; Dungga, Weny Almoravid; Wolok, Tineke; Yusuf, Barmin Rahmat; Anugrah, Krisna; Usman, Sartika Dewi; Santoso, Ivan Rahmat (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Tourism villages are tourism assets that are empowered and developed with all their uniqueness and attractiveness to attract tourist visits to the location of the village. The empowerment of Assisted Villages aims to apply the concept of community-based tourism in Bongo religious tourism village to Walima Festival tourism objects. The role of the community in this concept is very important for the sustainability of tourism. The use of community-based tourism methods can improve people's welfare in the economic sector. One of the interesting attractions in Bongo Tourism Village is the Walima Festival. Despite the uniqueness and advantages of this tourist attraction, it has not been managed properly. This activity goes through several stages, namely: planning, implementing, and evaluating the management of Walima Festival tourism objects, strengthening the role of the community, and technical guidance. The results show there is an increase in governance in Walima Festival tourism, local people's understanding of active participation in Walima Festival tourism, and an active role from the MSME sector as a craft provider and the Pokdarwis Group as a tour organizer.